Is there a proximal shift in the distribution of colorectal adenomas? - Oliveira, AM (2015)
INTRODUCTION: Several studies have shown a proximal shift of colorectal cancer (CRC) during the last decades. However, few have analyzed the changing distribution of adenomas over time. AIM: The aim of this study was to compare the site and the characteristics of colorectal adenomas, in a single center, during two periods. METHODS: We conducted a retrospective, observational study in a single hospital of adenomas removed during a total colonoscopy in two one-year periods: 2003 (period 1) and 2012 (period 2). Patients with inflammatory bowel disease, familial adenomatous polyposis, hereditary non-polyposis colorectal cancer syndrome, or history of CRC were excluded from the study. The χ(2) statistical test was performed. P values less than 0.05 were considered statistically significant. RESULTS: During the two considered periods, a total of 864 adenomas from 2394 complete colonoscopies were analyzed: 333 adenomas from 998 colonoscopies during period 1 and 531 adenomas from 1396 colonoscopies during period 2. There was a significant increase in the proportion of adenomatous polyps in the proximal colon from period 1 to 2 (30.6% to 38.8% (p = 0.015)). Comparing the advanced features of adenomas between the two periods, it was noted that in period 2, the number of adenomas with size ≥1 cm (p = 0.001), high-grade dysplasia (p = 0.001), and villous features (p < 0.0001) had a significant increase compared to period 1. CONCLUSION: Incidence of adenomatous polyps in the proximal colon as well as adenomas with advanced features has increased in the last years. This finding may have important implications regarding methods of CRC screening.